Investigating translation strategies in Indonesian best seller novel - Fata, Ika Apriani; Jannah, Miftahul; Daud, Bukhari; Muktabar, Fadhilah; Wahyuni, Sri (Englisia Journal, 2022)
Translation strategies have been the subject of extensive investigation. Most people believe that translators use specific strategies and that basic translation strategies are sometimes insufficient. As a result, numerous scholars have investigated and analyzed various translation techniques from various perspectives. This study determined the translation strategies in the novel of Negeri 5 Menara and its English Version, The Land of Five Towers using Baker's (2011) framework. This study was conducted using a descriptive qualitative technique to determine the translation strategies in Negeri 5 Menara and its English version, The Land of Five Towers. There were 130 data points in all. According to the findings, 11% about the use of the more general word, 14 % in the use of the more neutral or expensive word, 8% of cultural substitution, 5% of loan words, 4% of omission, paraphrase with related terms accounted for 57% of all translation tactics, while paraphrasing with unrelated words accounted for 2%, and there was no data on illustration. There were 21 uncategorized data points for every given strategy. It was predicted that in the future, a translator, who is also a pre-service teacher, should widen his or her translation methodologies in order to combat non-equivalence translation.